Stress-responsive gene regulation conferring salinity tolerance in wheat inoculated with ACC deaminase producing facultative methylotrophic actinobacterium - Meena, Kamlesh K.; Sorty, Ajay M.; Bitla, Utkarsh; Shinde, Akash L.; Kumar, Satish; Wakchaure, Goraksha C.; Kumar, Shrvan; Kanwat, Manish; Singh, Dhananjaya P. (Frontiers in Plant Science, 2023)
Microbes enhance crop resilience to abiotic stresses, aiding agricultural sustainability amid rising global land salinity. While microbes have proven effective via seed priming, soil amendments, and foliar sprays in diverse crops, their mechanisms remain less explored. This study explores the utilization of ACC deaminase-producing Nocardioides sp. to enhance wheat growth in saline environments and the molecular mechanisms underlying Nocardioides sp.-mediated salinity tolerance in wheat. The Nocardioides sp. inoculated seeds were grown under four salinity regimes viz., 0 dS m−1, 5 dS m−1, 10 dS m−1, and 15 dS m−1, and vegetative growth parameters including shoot-root length, germination percentage, seedling vigor index, total biomass, and shoot-root ratio were recorded. The Nocardioides inoculated wheat plants performed well under saline conditions compared to uninoculated plants and exhibited lower shoot:root (S:R) ratio (1.52 ± 0.14 for treated plants against 1.84 ± 0.08 for untreated plants) at salinity level of 15 dS m−1 and also showed improved biomass at 5 dS m−1 and 10 dS m−1. Furthermore, the inoculated plants also exhibited higher protein content viz., 22.13 mg g−1, 22.10 mg g−1, 22.63 mg g−1, and 23.62 mg g−1 fresh weight, respectively, at 0 dS m−1, 5 dS m−1, 10 dS m−1, and 15 dS m−1. The mechanisms were studied in terms of catalase, peroxidase, superoxide dismutase, and ascorbate peroxidase activity, free radical scavenging potential, in-situ localization of H2O2 and superoxide ions, and DNA damage. The inoculated seedlings maintained higher enzymatic and non-enzymatic antioxidant potential, which corroborated with reduced H2O2 and superoxide localization within the tissue. The gene expression profiles of 18 stress-related genes involving abscisic acid signaling, salt overly sensitive (SOS response), ion transporters, stress-related transcription factors, and antioxidant enzymes were also analyzed. Higher levels of stress-responsive gene transcripts, for instance, TaABARE ( +7- and +10-fold at 10 dS m−1 and 15 dS m−1); TaHAk1 and hkt1 ( +4- and +8-fold at 15 dS m−1); antioxidant enzymes CAT, MnSOD, POD, APX, GPX, and GR ( +4, +3, +5, +4, +9, and +8 folds and), indicated actively elevated combat mechanisms in inoculated seedlings. Our findings emphasize Nocardioides sp.–mediated wheat salinity tolerance via ABA-dependent cascade and salt-responsive ion transport system. This urges additional study of methylotrophic microbes to enhance crop abiotic stress resilience.